Anticancer Potential of Green Synthesized Silver Nanoparticles Using Extract of Nepeta deflersiana against Human Cervical Cancer Cells (HeLA) - Ebtesam S. Al-Sheddi; Nida N. Farshori; Mai M. Al-Oqail; Shaza M. Al-Massarani; Quaiser Saquib; Rizwan Wahab; Javed Musarrat; Abdulaziz A. Al-Khedhairy; Maqsood A. Siddiqui (Bioinorganic Chemistry and Applications)
In this study, silver nanoparticles (AgNPs) were synthesized using aqueous extract of Nepeta deflersiana plant. The prepared AgNPs (ND-AgNPs) were examined by ultraviolet-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscope (SEM), and energy dispersive spectroscopy (EDX). The results obtained from various characterizations revealed that average size of synthesized AgNPs was 33 nm and in face-centered-cubic structure. The anticancer potential of ND-AgNPs was investigated against human cervical cancer cells (HeLa). The cytotoxic response was assessed by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), neutral red uptake (NRU) assays, and morphological changes. Further, the influence of cytotoxic concentrations of ND-AgNPs on oxidative stress markers, reactive oxygen species (ROS) generation, mitochondrial membrane potential (MMP), cell cycle arrest and apoptosis/necrosis was studied. The cytotoxic response observed was in a concentration-dependent manner. Furthermore, the results also showed a significant increase in ROS and lipid peroxidation (LPO), along with a decrease in MMP and glutathione (GSH) levels. The cell cycle analysis and apoptosis/necrosis assay data exhibited ND-AgNPs-induced SubG1 arrest and apoptotic/necrotic cell death. The biosynthesized AgNPs-induced cell death in HeLA cells suggested the anticancer potential of ND-AgNPs. Therefore, they may be used to treat the cervical cancer cells.